Estrogen Modulation of MgATPase Activity of Nonmuscle Myosin-II-B Filaments - Gorodeski, George I. (2006)
The study tested the hypothesis that estrogen controls epithelial paracellular resistance through modulation of myosin. The objective was to understand how estrogen modulates non-muscle myosin-II-B (NMM-II-B), the main component of the cortical actomyosin in human epithelial cervical cells. Experiments used human cervical epithelial cells CaSki as a model, and end points were NMM-II-B phosphorylation, filamentation, and MgATPase activity. The results were as follows: 1) treatment with estrogen increased phosphorylation and MgATPase activity and decreased NMM-II-B filamentation; 2) estrogen effects could be blocked by antisense nucleotides for the estrogen receptor-α and by ICI-182,780, tamoxifen, and the casein kinase-II (CK2) inhibitor, 5,6-dichloro-1-β-(D)-ribofuranosylbenzimidazole and attenuated by AG1478 and PD98059 (inhibitors of epithelial growth factor receptor and ERK/MAPK) but not staurosporine [blocker of protein kinase C (PKC)]; 3) treatments with the PKC activator sn-1,2-di-octanoyl diglyceride induced biphasic effect on NMM-II-B MgATPase activity: an increase at 1 nM to 1 μM and a decrease in activity at more than 1 μM; 4) sn-1,2-dioctanoyl diglyceride also decreased NMM-II-B filamentation in a monophasic and saturable dose dependence (EC(50) 1–10 μM); 5) when coincubated directly with purified NMM-II-B filaments, both CK2 and PKC decreased filamentation and increased MgATPase activity; 6) assays done on disassembled NMM-II-B filaments showed MgATPase activity in filaments obtained from estrogen-treated cells but not estrogen-depleted cells; and 7) incubations in vitro with CK2, but not PKC, facilitated MgATPase activity, even in disassembled NMM-II-B filaments. The results suggest that estrogen, in an effect mediated by estrogen receptor-α and CK2 and involving the epithelial growth factor receptor and ERK/MAPK cascades, increases NMM-II-B MgATPase activity independent of NMM-II-B filamentation status.